A falência da razão: o fracasso da razão na Lettre à D Alembert sur le théâtre Français, de Jean-Jacques Rousseau - Lima, Flávio Campos de (2015)
The Letter to D'Alembert Jean-Jacques Rousseau written in the second half of the eighteenth century is an important text on the theater. The objective of this paper is to show the contradictions that according to Rousseau exists in the proposed D'Alembert to install a comedy theater in Rousseau's homeland, namely Geneva. The main contradiction to Rousseau existing in this proposal is the argument of D'Alembert as to whether this theater modeled on French power tune the habits and customs of the Genevan people, since their habits and customs are so different. For the comedy theater proposed to Geneva could tune the habits and customs of the Genevan citizens the reason would have to have effective effects on shows that were presented there, but according to Rousseau it does not. Considering that, for Rousseau the man to change their natural state to the welfare state has been corrupted, you can not tune the habits and customs of a people through imitative and performing arts as it tries to sustain D'Alembert, moreover, Paris to see Rousseau is a great degenerate and depraved city, Geneva in turn, is a small town that still preserves the moderate customs and where the people are quiet. Thus, Rousseau says it is not possible to be silent before such an event